Viet Nam: Business opportunities and risks - Quinlan, Joseph P. (Berkeley Pacific View Press, 1995)
This groundbreaking book provides what every company considering the market needs: equal doses of insight, realism, and practical first steps
Keywords: Quản trị kinh doanh